Indefinite least squares with a quadratic constraint - Gonzalez Zerbo, Santiago; Maestripieri, Alejandra; Martínez Pería, Francisco (Journal of mathematical analysis and applications, 2022)
An abstract indefinite least squares problem with a quadratic constraint is considered. This is a quadratic programming problem with one quadratic equality constraint, where neither the objective nor the constraint is a convex function. Necessary and sufficient conditions are found for the existence of solutions.